2021
DOI: 10.1161/atvbaha.120.315255
|View full text |Cite
|
Sign up to set email alerts
|

Local M-CSF (Macrophage Colony-Stimulating Factor) Expression Regulates Macrophage Proliferation and Apoptosis in Atherosclerosis

Abstract: Objective: Previous studies have shown that deficiency of M-CSF (macrophage colony-stimulating factor; or CSF1 [colony stimulating factor 1]) dramatically reduces atherosclerosis in hyperlipidemic mice. We characterize the underlying mechanism and investigate the relevant sources of CSF1 in lesions. Approach and Results: We quantitatively assessed the effects of CSF1 deficiency on macrophage proliferation and apoptosis in atherosclerotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 50 publications
2
38
0
1
Order By: Relevance
“…Oxidized LDL provokes colonystimulating factor 1 (Csf1) secretion by endothelial cells, for example [44]. A recent study described increased macrophage survival and proliferation in the plaque in response to Csf1 production by endothelial cells and vascular smooth muscle cells, in particular [57]. This may represent an additional, indirect mechanism by which statins, via systemic reduction in cholesterol-rich LDL particle numbers, inhibit lesional macrophage proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidized LDL provokes colonystimulating factor 1 (Csf1) secretion by endothelial cells, for example [44]. A recent study described increased macrophage survival and proliferation in the plaque in response to Csf1 production by endothelial cells and vascular smooth muscle cells, in particular [57]. This may represent an additional, indirect mechanism by which statins, via systemic reduction in cholesterol-rich LDL particle numbers, inhibit lesional macrophage proliferation.…”
Section: Discussionmentioning
confidence: 99%
“… 71 72 Recently, it has been shown that CSF-1 derived from local smooth muscle and endothelial cells supports plaque macrophage survival. 73 In addition, rapid adaption and differentiation of monocytes in plaques requires CSF-1 receptor-mediated signaling in aortic stromal cells and macrophages. 71 72 Among the various subsets of monocytes, CD14 + CD16 ++ monocytes are associated with maintaining the vasculature, cell survival, and localization within plaques through CX3CR1/CX3CL1 interactions in atherosclerosis.…”
Section: Monocyte-derived Macrophages In Atherosclerosismentioning
confidence: 99%
“…Once monocytes access the peripheral tissues, they differentiate to macrophage populations and require CSF-1 for their survival and maintenance [ 51 , 52 ]. It was recently found that production of CSF-1 that supports plaque macrophage survival comes from local smooth muscle and endothelial cells, not from systemic production [ 53 ]. The topics of transition of Ly6C hi monocytes to macrophages in pathological conditions (e.g., atherosclerosis) are discussed below.…”
Section: Monocyte Recruitment and Specificationmentioning
confidence: 99%